Information visualization analysis of international Taijiquan patent technology field - Jiang, Yanan; Shen, Guoqing; Liu, Qingqun (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: On December 17, 2020, Chinese Taijiquan was included in the list of representative works of human intangible cultural heritage, and the internationalization of Chinese Taijiquan entered a new stage. By consulting the related literature of Taijiquan, it is found that there is no relevant patent analysis of Taijiquan. Patent is a kind of exclusive power protected by the legal system that highlights the vitality of innovation in this field. It contains technical, legal and economic information, and is a rare comprehensive information resource. The analysis of international Taijiquan related patents can obtain the latest development of international Taijiquan patents, and provide reference and reference for the output of my country's Taijiquan patent technology. At the same time, it provides a new perspective for the research on the status quo of Taijiquan's international dissemination and recognition, and provides a new idea for the better exploration, interpretation and innovation of Taijiquan culture, and even for the development of Taijiquan's industrialization. Methods: (1) The document data method: Searching in CNKI, using "Tai Chi" and "Sports Patent" as keywords (search time range: 2010-2021), with "TS=(tai chi OR) taichi OR tai ji OR taiji OR tai ji chuan OR taijichuan OR tai ji quan OR tajiquan OR tai chi quan OR taichiquan)" is the search condition for advanced search in the Derwent index database. In the library of Zhengzhou University and the library of Zhengzhou University Sports College, you can read books about Taijiquan, patent technology, and knowledge graph visualization, and check and browse related websites of Taijiquan, patent and knowledge graph visualization. After reading, sorting and summarizing the above-mentioned documents, 15 of them are directly cited as the theoretical support for the analysis of international Taijiquan patents. (2) Bibliometric and visual analysis method: This article uses Citespace (5.6.R2) visualization software to visually analyze international Taijiquan related patents, combining quantitative research with qualitative research. Visually analyze the annual number of patents, the distribution of DMC patent technology fields and the hotspot evolution trend of international Taijiquan patents included in the Derwent database from 1963 to 2021, and provide a more intuitive and clear research and analysis of the development and future evolution of international Taijiquan patents trend. (3) Logic analysis method: Organizing, summarizing, and analyzing data and information related to international Taijiquan patents. Results: From the perspective of the time distribution of international Taijiquan patents, through the analysis of the annual publication volume of international Taijiquan patents, the annual number of international Taijiquan patent applications has shown a fluctuating growth trend.The spatial distribution of international Taijiquan patents is as follows: (1) From the perspective of the distribution of disciplines, the international Taijiquan patent technology covers a total of 18 disciplines from 1963 to 2021, mainly involving the fields of instrumentation, sports science, engineering design, and telecommunications technology. Computer science and other fields. Among them, Taijiquan patents involve the most in the field of equipment, with a total of 356. (2) From the perspective of the distribution of patentees, there were a total of 288 patentees for international Taijiquan patents from 1963 to 2021, and the top 19 patentees were all from China. Among them, 10 patents are for individual applications, 7 are for university applications, and 2 are for company applications. The patentees of international Taijiquan patents are mainly individuals and schools, and the output of Taijiquan patents that rely on companies is relatively small. (3) From the distribution of main inventors, 454 inventors participated in the international Taijiquan patents from 1963 to 2021. Compared with the number of patents of other sports, there are relatively few inventors involved in the research and development of Taijiquan in the world. However, an analysis of the top 20 inventors of international Taijiquan research found that these patented inventors are all from China. The analysis of the hot technical fields of international Taijiquan patents is as follows: (1) From the perspective of the IPC technology distribution of international Taijiquan patents, international Taijiquan patents involve a total of 228 technical fields, involving A human life needs, B operations; transportation, C chemistry; Metallurgy, F Mechanical Engineering; Lighting; Heating; Weapons; Blasting, G Physics, and H Electricity. Among them, Part A has the largest number of patents on human life needs, with a total of 140 patents, accounting for 61.40% of the total number of Taijiquan patents. IPC hotspot technical fields mainly belong to A63B (equipment for physical exercise, gymnastics, swimming, climbing or fencing; balls; training equipment). (2) Judging from the distribution of international Taijiquan patent DMC, the technical fields with the highest frequency of international Taijiquan patent technology are sports training and fitness training, training equipment, and computer processing for sports and training equipment. The simultaneous appearance of multiple codes in a patent indicates that a patent can be applied to multiple technical fields. The main hot areas of Derwent manual code patent technology mainly focus on the equipment, equipment and clothing in Tai Chi exercise training. The patent direction is mainly Tai Chi fitness and teaching, but also involves the field of athletics and medical treatment. The distribution of core patents of international patent technology is as follows: (1) Judging from the distribution of the top 15 core patents cited by frequency, the core patents of international Taijiquan are mainly concentrated in China and the United States, and China has the most cited high-frequency documents. According to the analysis of patent themes, it is found that more patents are developed for fitness functions in Taijiquan, and there are fewer patent developments in sports. Except for related patents specifically designed for Taijiquan, most of the patents whose functions can be applied to the field of Taijiquan as well as other fields. (2) From the perspective of the distribution of the main patentees of core patents, the main patentees of core patents mostly belong to China and the United States. China has certain advantages in the research of core patents of Taijiquan. The patentees of core patents are mostly companies and colleges. Conclusion: (1)Although the applications for international Taijiquan patents have not formed a continuous upward trend year by year, they still show an overall increasing trend. (2) Taijiquan has its own limitations. Compared with other sports, patents involve fewer disciplines, but the patented technology of Taijiquan still has the characteristics of cross-integration of multidisciplinary research fields. In addition to the overall characteristics of Taijiquan related patents that are multidisciplinary, their single patents also involve multiple disciplines. (3) Compared with the most market-oriented and industrialized sports events such as basketball, tennis, badminton, etc., which are mostly owned by the company in the world, Tai Chi is still a sports event with a strong local color, with a degree of internationalization. While relatively low, the market conversion rate is low, and the patent utilization rate is low. (4) China has a large number of patented Taijiquan inventors and is the main force in Taijiquan patented inventions. Most of the invention patent outputs of the main patent inventors come from individuals or relying on schools, and some inventors have a common invention cooperation group, and they have continuous cooperation outputs of Taijiquan patents. (5) From the perspective of the types of international patent classification codes, international Taijiquan patents cover a wide range of functional areas. From the perspective of patented technical topics, patent research and development are mainly focused on training equipment. (6) The development of core patents pays more attention to the fitness value of Tai Chi. With the financial support of the company and the school and the guarantee of scientific research, the core patents of Taijiquan can be produced better.